Expression of sodium-iodide symporter in thyroid gland tumors: immunohistochemical study - Bondarenko O.O.; Shponka I.S.; Shponka V.I. (Морфологія, 2009)
One of the key moments of radioiodine therapy, and also radioisotope diagnostics of cancers of a thyroid gland is ability of their cells to accumulate iodide. This ability is provided with activity of the specific transporter – sodium-iodide symporter. Our research has shown disorders of sodium-iodide symporter immunoexpression in all tumors of thyroid gland: from overexpression and absence of plasma membrane expression in differentiated carcinomas, up to weak or actually absent in low differentiated cancers and Hurtle-cells tumors. Thus, there is a prospect of application of the sodium-iodide symporter, as the prognostic marker of thyroid cancers.